The Perception and Challenges of Airport Ground Staff Towards the Use of English Language at Pattimura International Airport - Siwa, Arleyd Zamer Marcelino (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2023)
This study investigates the perceptions and challenges of airport ground staff regarding English language usage at Pattimura International Airport, Indonesia. Using an explanatory sequential mixed-methods design, data were collected from 30 front-line airport staff through questionnaires and in-depth interviews. The quantitative analysis revealed unanimous recognition (100%) of English as essential for airport operations, while qualitative findings provided deeper insights into implementation challenges. Key findings indicate that despite positive perceptions toward English usage, staff face significant challenges in speaking (60% reporting anxiety) and listening comprehension (40% reporting language conversion difficulties). The absence of formal language training (reported by 100% of participants) has led to reliance on self-directed learning strategies. Staff primarily utilize informal methods such as watching movies with subtitles and listening to English songs to improve their language skills. This study highlights a critical gap between institutional requirements and support systems in English language development at the airport. These findings have important implications for aviation language training policies and suggest the need for structured institutional support to enhance staff English proficiency and confidence in professional communication.